Vývojové tendence hospodářských soustav - Paulík, Tibor (Univerzita Pardubice, 1999)
The article characterises the development of the economic systems, identifies the economic coordination mechanism, dilemma of the market economy co-ordination and margins of the market economy with the help of some perspectives of the economic ethics.
Keywords: Ekonomika; hospodářské systémy; vývoj; tržní hospodářství